The Retrochiasmal Optic Pathway: A Link in Jeopardy - Campos, Manuel; Drapkin, Allan J. (Frontiers in Surgery, 2020)
The case of an intraventricular meningioma is presented and the visual complication incurred by its surgical resection is discussed. The importance of selecting the most optimal surgical approach and the basis for that selection are highlighted.